An occupational health survey of sewage treatment plant workers of Dakshina Kannada, Karnataka - Haleema, Mubeena; Bhargava, Madhavi; Nirgude, Abhay S.; ., Irfan (International Journal Of Community Medicine And Public Health, 2019)
Background: Sanitation workers are at a risk of exposure to various health hazards which are preventable. The present study aimed at assessing the health status of sewage treatment plant (STP) workers, their respiratory morbidity and onsite assessment of their occupational safety. Methods: A cross sectional study was conducted in a single STP during June-July months of 2017. A total of 32 employees were enrolled in the study. Data collection was done using a questionnaire, clinical examination and onsite assessment for occupational safety. The questionnaire included demographic details, clinical symptoms and use of personal protective equipment (PPE). Clinical examination with special focus on respiratory system and portable spirometry was conducted followed by health education on workplace safety. Descriptive statistics were reported as mean and standard deviation for continuous variables and frequency and proportion for categorical variable. Results: None of the workers underwent pre-placement health check-up and routine health check-ups at regular interval. PPE were available in adequate number. Spirometry revealed 12 workers having forced expiratory volume in one second/forced vital capacity (FEV1/FVC) within normal limits and seven workers with mild restriction. Early small airway obstruction was found in six workers. Regarding the on-site safety, an absence of barricades at two places near anaerobic sludge reactor and clarifier tank was of concern. Conclusions: The workers in STP are at risk of respiratory occupational hazards and should undergo pre-placement and routine health check-up for prevention of occupational hazards. Physical safety in terms of barricades at appropriate sites also needs attention.